2010
DOI: 10.1073/pnas.0914627107
|View full text |Cite
|
Sign up to set email alerts
|

How grandmother effects plus individual variation in frailty shape fertility and mortality: Guidance from human–chimpanzee comparisons

Abstract: In the first paper to present formal theory explaining that senescence is a consequence of natural selection, W. D. Hamilton concluded that human postmenopausal longevity results from the contributions of ancestral grandmothers to the reproduction of their relatives. A grandmother hypothesis, subsequently elaborated with additional lines of evidence, helps explain both exceptional longevity and additional features of life history that distinguish humans from the other great apes. However, some of the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 107 publications
(122 reference statements)
2
45
1
Order By: Relevance
“…Thus, many extant human phenotypic traits evolved in response to selection forces that have, over the past 100 years, greatly changed. To examine the evolutionary dynamics of humans prior to the industrial revolution, we examine the life table for primitive humans [28]. When these data are used to parametrize our model, we predict that early humans would, relative to elephants and naked mole rats, have lower cancer suppression and less likelihood of dying from cancer relative to other sources of mortality.…”
Section: (H) Humans and Cancermentioning
confidence: 99%
“…Thus, many extant human phenotypic traits evolved in response to selection forces that have, over the past 100 years, greatly changed. To examine the evolutionary dynamics of humans prior to the industrial revolution, we examine the life table for primitive humans [28]. When these data are used to parametrize our model, we predict that early humans would, relative to elephants and naked mole rats, have lower cancer suppression and less likelihood of dying from cancer relative to other sources of mortality.…”
Section: (H) Humans and Cancermentioning
confidence: 99%
“…That argument relates to a longstanding view, expressed by JBS Haldane, Peter Medawar and others, that phenotypes associated with ageing lie outside the reach of natural selection. Notwithstanding the 'grandmother' effect that could operate postreproductively via kin selection [6,86], the observation that BCC and SCC are mostly benign or post-reproductive in character is misleading. The observation is essentially correct in the context of contemporary white-skinned Caucasians inhabiting temperate United States [44] or subtropical zones (for example Queensland, Australia, at 10-208 latitude) [22].…”
Section: Ancestral Environments and Skin Colorationmentioning
confidence: 99%
“…Given the important role of telomere caps at chromosomal ends in modulating cell survival, ageing and cancer [55,56], it was reasonable to look for a difference in humans. Paradoxical to the finding of extended lifespan in humans [32,57], telomere lengths were found to be greater in nonhuman primates than in humans, and telomere shortening rates were not apparently different between humans and chimpanzees [58,59]. Given the importance of genome damage and DNA repair in cancer, it is also interesting that one study indicated that humans and chimpanzees differ in their cellular response to DNA damage and noncoding sequence elements of DNA repair-associated genes, with evidence for accelerated evolution in some promoter regions and introns [60].…”
Section: Genetic Susceptibilitymentioning
confidence: 99%